MODEL PENEMUAN TERBIMBING UNTUK MENGIDENTIFIKASI KEKURANGAN TEKS PROSEDUR SISWA KELAS VIII SMPN 1 KARANGPLOSO - Diah Erna Triningsih (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
The purpose of this study was to describe the learning procedure to identify deficiencies text guided discovery methods class VIII SMP Negeri 1 Karangploso. This study used a qualitative descriptive study. The results showed (1) model of guided discovery can be used for learning to identify the drawback text procedures, (2) RPP are designed teacher right good basic competencies, indicators, learning objectives, materials, lesson, source, medium, and apparatus as well as the design of attitude assessment and knowledge appropriate to reach KD, (3) determining the allocation of time on the basis of competence and promissory prota less precise, (4) assessment of the results overlap with text revising skills assessment procedure.